What we can find out from CEO letters? - Vettenranta, Krista (My University, 2017)
This study examines the question of what kind of information we can find out from CEO letters. This study makes analogy between annual and sustainability reports. The data identify by a variety of criteria for example are the companies reporting in accordance with the Global Reporting Initiative –guideline or not and the age of CEOs. The data of this study includes CEO letters which have published in annual and sustainability reports. Data includes reports from 30 Finnish companies which are operating in three sectors, financial services, forest and paper products and energy. The data is from the years 2006 - 2015 as a longitudinal perspective. The results shows as sentiment analysis focus on the use of natural language processing. The analysis shows that the rhetoric used in CEO letters can change because of many reasons. This study analyses the reasons why the rhetoric used in CEO letters can change over the years. In addition, the difference between the sectors analyze with the t-test shows statistical significant difference between two sectors.
Keywords: sustainability reporting; sentiment analysis; CEO letters; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Laskentatoimen ja tilintarkastuksen maisteriohjelma|en=Master's Programme in Accounting and Auditing|